Energy availability, macronutrient intake, and nutritional supplementation for improving exercise performance in endurance athletes - Casazza, G. A.; Tovar, A. P.; Richardson, C. E.; Cortez, A. N.; Davis, B. A. (Current Sports Medicine Reports, 2018)
Endurance athletes use nutritional guidelines and supplements to improve exercise performance and recovery. However, use is not always based on scientific evidence of improved performance, which type of athlete would benefit most, or the optimal dose and timing of a particular supplement. Health professionals that give advice to athletes need to target their recommendations on the energy systems and muscle fiber types used for the athlete`s sporting event, the goal of the training block, the time of the competitive season, and the characteristics and food preferences of the individual athlete. This review aims to summarize the most current research findings on the optimal calorie, carbohydrate, and protein intake for athlete health, performance, and recovery. We also summarized new findings on fluid intake and the optimal dose and timing of beetroot and caffeine supplementation on time trial performance in endurance athletes.